2011
DOI: 10.1007/s12033-011-9426-2
|View full text |Cite
|
Sign up to set email alerts
|

Over Expression of Rice chitinase Gene in Transgenic Peanut (Arachis hypogaea L.) Improves Resistance Against Leaf Spot

Abstract: A Rice chitinase-3 under enhance version of CaMV 35S was introduced into peanut (Arachis hypogaea L.) through Agrobacterium mediation. Agrobacterium tumefaciens strain LB4404 was used harboring the binary vector (pB1333-EN4-RCG3) containing the chitinase (chit) and hygromycin resistance (hpt) gene as selectable marker. Putative transgenic shoots were regenerated and grown on MS medium supplemented with 5 mg/l BAP, 1 mg/l kinetin, and 30 mg/l hygromycin. Elongated shoots were examined for the presence of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
50
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 21 publications
0
50
0
1
Order By: Relevance
“…It was shorter than the 120Á150 d reported by Sharma and Anjaiah (2000), Sharma and Ortiz (2000). Although Agrobacteriummediated transformation of peanut was reported previously, these studies revealed a marked disparity between the conditions considered to enable optimal efficiency of transformation (Li et al 1997;Rohini and Sankara 2001;Anuradha et al 2006;Tiwari et al 2008;Yang et al 2011;Iqbal et al 2012). The present study demonstrated that factors such as the choice of genotype, source of explants, efficiency of the interaction of Agrobacterium with cells of the target tissue, and a reproducible complete plant regeneration protocol are crucial for successful transformation of peanut.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…It was shorter than the 120Á150 d reported by Sharma and Anjaiah (2000), Sharma and Ortiz (2000). Although Agrobacteriummediated transformation of peanut was reported previously, these studies revealed a marked disparity between the conditions considered to enable optimal efficiency of transformation (Li et al 1997;Rohini and Sankara 2001;Anuradha et al 2006;Tiwari et al 2008;Yang et al 2011;Iqbal et al 2012). The present study demonstrated that factors such as the choice of genotype, source of explants, efficiency of the interaction of Agrobacterium with cells of the target tissue, and a reproducible complete plant regeneration protocol are crucial for successful transformation of peanut.…”
Section: Discussionmentioning
confidence: 80%
“…The regeneration percentage of shoots from cotyledons was slightly lower than that of the shoots from mesocotyl but a considerably higher transformation efficiency was obtained with mesocotyl-derived explants than the efficiency obtained with cotyledonderived explants. Most previous studies of Agrobacteriummediated transformation of peanut have used leaf discs, cotyledons, cotyledonary nodes, and embryo axes as target tissues (Eapen and George 1994;McKently et al 1995;Cheng et al 1996;Gelvin 2003;Anuradha et al 2006;Iqbal et al 2012). Cotyledon-derived explants are suitable for the transformation and regeneration of fertile plants, including crop species such as chickpea, rape, and peanut (Moloney et al 1989;Sharma and Anjaiah 2000;Sharma and Ortiz 2000;Bhattacharjee et al 2010;Iqbal et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations